A profile of glenohumeral internal and external rotation motion in the uninjured high school baseball pitcher, part I: motion - Hurd, W. J.; Kaplan, K. M.; EI Attrache, N. S.; Jobe, F. W.; Morrey, B. F.; Kaufman, K. R. (Journal of Athletic Training, 2011)
Context: The magnitude of motion that is normal for the throwing shoulder in uninjured baseball pitchers has not been established. Chronologic factors contributing to adaptations in motion present in the thrower's shoulder also have not been established.